ACTORS AND NETWORKING ON TVET QA SYSTEM OF THAILAND: A STUDY ON THE IMPLEMENTATION AND ITS PROBLEMS - Thepmondhri, Rangsan; Chuo-Chun, Hsieh; Chih-Wen, Fan (PEOPLE: International Journal of Social Sciences, 2018)
This research was conducted to study the Technical and Vocational Education and Training (TVET) Quality Assurance (QA) system in Thailand, its implementation, and its problems from 2000-2015 focusing primarily on the actors and their networking. Interviews were conducted with a purposeful sampling of participants who were from both the Office of the Vocational Education Commission (OVEC) and the colleges located in different regions of Thailand. Institutional Analysis and Development (IAD) Framework was used as a theoretical reference. The research found that internal TVET QA board committee of the OVEC and the external TVET QA board committee of the Office for National Education Standards and Quality Assessment (ONESQA) were the main policy actors. All actions and contributions of the OVEC and the ONESQA officials and staff, including internal and external assessors, were recognized as a minor role comparing to those board committees of the OVEC and the ONESQA and people at the colleges. At the colleges, administrators and teachers were expected to implement TVET QA. However, their exact roles and duties were not well defined. Networking among the OVEC, the ONESQA, the colleges, and other supporting personnel was limited and focused solely on the assessment. Implementation of the TVET QA system was accepted as a viable means of quality development. However, there was speculation that the cost of implementing the system outweighed the benefits of it. There was concern over the absence of individual or institutional benefits. However, these concerns were not perceived as obstructive or problematic to the implementation of the TVET QA system. The implementation of the TVET QA system could have been greatly improved if the mechanisms by which information was shared, communication, and networking between actors were made more efficient.